Pemeliharaan Generator Pada Turbin PLTMH (Pembangkit Listrik Tenaga Mikro Hidro) di PT. Perkebunan Nusantara VI Jambi: Maintanance of Generator on Turbine HPP (Micro Hydro Power Plant) at PT. Plantation Nusantara VI Jambi - Hendrick, Fran (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2022)
Generator or alternator is a unit or machine that can be used as a machine that can convert motion or mechanical energy into electrical output with the work of electromagnetic induction. Generator work is good because of good maintenance as well. Problems that often occur at PT Perkebunan Nusantara VI are usually caused by machines that work continuously, the age of the machine, damage caused by nature such as rainwater that causes corrosion, and weak or peeling insulators, high or low voltages, and other visual damage. The purpose of this maintenance is to prevent damage to the machine so that good production results and produce structured maintenance on the machine. The method used is to prevent and perform good maintenance using the TPM (Total Productive Maintenance) method, where this method can improve the quality of maintenance and prevent repeated machine damage so that the company's productivity results run optimally. The results of maintenance using this TPM method which creates a structured maintenance with standardization of company maintenance and makes this TPM method a maintenance principle to create good product results.